Optimization of back ITO layer as the sandwiched reflector for exploiting longer wavelength lights in thin and flexible (30 µm) single junction c-Si solar cells - Kumar Dikshit A.; Chandra Mandal N.; Bose S.; Mukherjee N.; Chakrabarti P. (My University, 2025)
Fabrication of thin and flexible crystalline silicon solar cells based on single junction concept is reported with detailed investigations on each step of the production flow chain. With the aim of minimizing material use/wastage as per the international technology roadmap for photovoltaic (ITRPV), which is also directly related to the device cost, efforts have been made to introduce thin (~30 µm) c-Si wafers instead of a conventional 180 µm wafer to fabricate single-junction solar cells. Due to the introduction of thin (~30 µm) c-Si wafer, the device becomes flexible, which is also an additional benefit towards the development of future roll-to-roll electronics. In order to address better carrier collection in thin silicon as well as light management, measures have been taken by introducing an indium tin oxide (ITO) layer both on top and at the bottom. The influence of this ITO layer along with back Al contact toward the cell efficiency has been discussed. X-ray diffraction (XRD) analysis has been carried out to investigate microstrain and dislocation density related changes in the thin wafer, which are known to have influence on the photoconversion efficiency. Under 1 Sun illumination, current – voltage characteristics and external quantum efficiency were measured and found to be promising. © 2019 International Solar Energy Society